Clinical outcomes in patients with systemic lupus erythematosus treated with belimumab in clinical practice settings: a retrospective analysis of results from the OBSErve study in Switzerland - Johannes von Kempis; Sabine Duetsch; Nicola Reuschling; Rahel Villiger; Peter M Villiger; Florence Vallelian; Dominik J Schaer; Ruediger B Mueller (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY